2020
DOI: 10.1021/acs.joc.0c00771
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Quinazolin-4-ones by Copper-Catalyzed Isocyanide Insertion

Abstract: Herein, we report a novel copper-catalyzed imidoylative cross-coupling/cyclocondensation reaction between 2-isocyanobenzoates and amines efficiently producing quinazolin-4-ones. The reaction utilizes Cu­(II) acetate as an environmentally benign catalyst in combination with a mild base and proceeds well in anisole, a recommended, sustainable solvent. Additionally, the reaction does not require dry conditions or inert atmospheres for optimal performance. The scope of this isocyanide insertion reaction is rather … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…In recent years, the isocyanide insertion strategy under non‐metal, Lewis‐acid, base and photocatalyzed reaction conditions become familiar in the field of organic synthesis [8,12] . It is noteworthy that the isocyanide insertion chemistry under transition metal‐free and non‐transition metal‐free conditions are very rare and remained asserting task for the synthetic chemists [8–12] . In particular, utilizing isocyanides as C1‐source has always been explored under transition metal‐catalysis [13–15] .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In recent years, the isocyanide insertion strategy under non‐metal, Lewis‐acid, base and photocatalyzed reaction conditions become familiar in the field of organic synthesis [8,12] . It is noteworthy that the isocyanide insertion chemistry under transition metal‐free and non‐transition metal‐free conditions are very rare and remained asserting task for the synthetic chemists [8–12] . In particular, utilizing isocyanides as C1‐source has always been explored under transition metal‐catalysis [13–15] .…”
Section: Methodsmentioning
confidence: 99%
“…[1a] A large number of useful reports have been noticed on isocyanide insertion owing to their reactivities and efficiencies. In literature, it has been shown that the isocyanides have been utilized as CÀ NÀ C, [4][5][6][7][8][9] CÀ N [10][11][12] and C1-source [13][14][15] to construct various complex molecules (Scheme 1).Further, the reported methodologies are mainly concerned on using the transition metals such as Pd, [4,13,15] Cu, [5,11] Co [6] and Ni. [7,14] In recent years, the isocyanide insertion strategy under non-metal, Lewis-acid, base and photocatalyzed reaction conditions become familiar in the field of organic synthesis.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[2] Therefore, numerous elegant synthetic routes have been established for the assembly of structurally diverse quinazolin-4(3H)-ones in the past decades. [3] The most frequently used strategies lie in the condensation reactions of benzoic acid derivatives and also palladium-catalyzed carbonylative cyclization reactions of 2-haloanilines. [4] Palladium-catalyzed carbonylative transformations have emerged as a powerful and straightforward pathway for the synthesis of various carbonyl-containing heterocycles.…”
Section: Introductionmentioning
confidence: 99%